Flood risk assessment: a review - TE Ologunorisa; MJ Abawua (Journal of Applied Sciences and Environmental Management, 2005)
The paper reviews some of the techniques of flood risk assessment using case studies from different countries in the world. These techniques are meteorological, hydrological, hydrometeorological, socio-economic and those based on Geographic Information System (GIS). The paper concludes that GIS technique appears to be most promising as it is capable of integrating all the other techniques of flood risk assessment.